Cilostazol Improves Proangiogenesis Functions in Human Early Endothelial Progenitor Cells through the Stromal Cell-Derived Factor System and Hybrid Therapy Provides a Synergistic Effect In Vivo - Shih-Ya Tseng (BioMed Research International, 2016)
This study investigated the effect of cilostazol on proangiogenesis functions in human early endothelial progenitor cells (EPCs) in vitro and the therapeutic implication of hybrid therapy with cilostazol and human early EPCs in vivo. Cilostazol significantly increased colony-forming units and enhanced differentiation of EPCs toward endothelial lineage. Treatments resulted in antiapoptotic effects and stimulated proliferation and migration and in vitro vascular tube formation through activation of stromal cell-derived factor-1 (SDF-1)/C-X-C chemokine receptor type 4 (CXCR4)/phosphatidylinositol-3 kinase (PI3K)/Akt signaling pathway. Blood flow recovery and capillary density in murine ischemic hindlimbs were significantly improved in cilostazol-treated, human early EPCs-treated, and cotreatment groups. The effects were attenuated with SDF-1α inhibition. Plasma SDF-1α levels were significantly higher in 3 active treatment groups after surgery, with greatest effects observed in hybrid therapy. The angiogenic effects of transplanted EPCs pretreated with cilostazol ex vivo were superior to untreated EPCs using in vivo Matrigel assay. Implanted EPCs were incorporated into the capillary, with pretreatment or cotreatment with cilostazol resulting in enhanced effects. Taken together, cilostazol promotes a large number of proangiogenic functions in human early EPCs through activation of SDF-1/CXCR4/PI3K/Akt signaling, and hybrid therapy provides a synergistic effect in vivo. Cotreatment may be beneficial in ischemic disease.